An unusual case of loculated malignant pleural effusion mimicking an infected pericardial cyst - Nimje, Varun; Bodhankar, Shubham; Yadav, Tushar (Indian Journal of Case Reports, 2022)
Malignant pleural effusion (MPE) is one of the frequent and distressing conditions identified at the advanced stage of different malignant conditions. This problem seems to affect patients with lung and breast malignancies which contribute to the lower life quality. Less commonly MPE presents as a loculated fluid collection. We present an unusual case of cystic fluid collection in contact with the heart appearing similar to a pericardial cyst, but on cytological examination turned out to be loculated MPE. Furthermore, there was the presence of malignant fissural effusion. This text highlights the unusual location of this loculated MPE along with a few characteristic features to differentiate it from the benign pericardial cyst.